The Expatriates – Spatriati – and the South as a Bridging “Territory of the Soul”. Interview with Mario Desiati conducted by Dagmar Reichardt - Reichardt, Dagmar; Desiati, Mario (TransCulturale, 2023)
Italian Strega Prize winner 2022 Mario Desiati focuses on “the” South defined by Apulian expats as symbolic protagonists of his award-winning novel. The Spatriati stand for a chance to develop and grow.